Perilaku Belanja Online Produk Umkm Pada Masa Pandemi Covid-19 di Kalangan Generasi Milenial - Rita Yustika; Popy Novita Pasaribu (Diversity: Jurnal Ilmiah Pascasarjana, 2022)
In line with the increasingly rapid development of the world of information and communication supported by increasingly sophisticated technology, it encourages us to find out how the motivation for online shopping from consumers is for MSME products during the Covid-19 pandemic in the milenial community around the Jabodetabek area. Quantitative research methods were objective with a deductive processed, research is designed to discuss problems that have been determined from the beginning and did not change until the end of the study and were static from beginning to end. The total respondents were 174. Data processing was carried out by using multiple regression analysis with software of SPSS 26.0 on respondents aged 25 years showing that the results obtained simultaneously; perceived usefulness, hedonic motivation, internal norms, external subject norms, and the Covid-19 pandemic have a significant effect on the motivational behavioral intentions of online shopping for MSME products by millennials in the Jabodetabek area. The results of the partial test, the hedonic motivation factor was proven to have a positive and significant influence on the intention of online shopping behavior for MSME products among millennials generation in Jabodetabek